Infidels and Empires in a New World Order: Early Modern Spanish Contributions to International Legal Thought - Lantigua, David M. (Law and Christianity, 2020)
Examines early modern Spanish contributions to international relations by focusing on ambivalence of natural rights in European colonial expansion to the Americas.